The effect of number of tanks on water quality in rainwater harvesting systems under sudden contaminant input - Dissanayake, J.; Han, M. (Elsevier, 2021)
Rainwater harvesting (RWH) is a sustainable solution for curbing existing urban water crises. Many countries have implemented various design guidelines for RWH systems, but water quality issues persist, especially with respect to particulate matter and soluble contaminants entering the RWH system after a prolonged dry period. A first-flush unit in an RWH system can partially manage this sudden influx of pollutants, provided that rainfall conditions are favorable for its optimal operation. Therefore, a significant proportion of these pollutants reach the storage tank. The most common single storage tank RWH systems accumulate particulate matter, and allow soluble and particulate contaminants to reach the outlet quickly at undesirably high concentrations. To overcome these issues pertaining to single tank systems, multiple tank systems with similar volumes have been implemented globally. However, limited research has been conducted to assess the effect of the number of tanks on harvested water quality under a sudden pollutant input. Hence, the authors have investigated the effect of the number of tanks on particulate matter distribution in multi-tank systems, and observed that more than 60% of the particle mass input was retained in the first tank. By increasing the number of tanks, the particle mass reaching the final tank becomes constant despite changes in the flowrate and influx particle mass. Furthermore, a soluble contaminant entering a multi-tank system was observed to reside within the system for a prolonged time by approximately a factor of two, which is favorable for developing a response strategy. It is recommended by the authors that at least three tanks should be used to gain the benefits of a multiple-tank RWH system.